Orientation, Organizational Capability, Organizational Coordination and Cooperation as Predictor of Long-term Orientation: Examining the Mediating Role of Supply Chain Management - M. Farid Wajdi; Achmad Aminudin; Basworo Dibyo (International Journal of Supply Chain Management, 2020)
The main focus of this study was to explore the relationship between supply chain management, organizational coordination, cooperation, organizational capability and long-term orientation. Moreover, the study also evaluated the mediating impact of supply chain management between organizational coordination, cooperation and organizational capability and long-term orientation. The data for this study was collected from the workers working in restaurants in Indonesia. The data was collected through questionnaires. The response rate of the present study was 69%. The collected data was analysed through PLS-SEM. The findings of the study revealed that supply chain management and long-term orientation are directly impacted by organizational coordination, cooperation and organizational capability. Moreover, supply chain management also mediates among organizational coordination, cooperation and organizational capability. By using the findings of the study are important for the strategic and decision-makers of the supply chain industry. Moreover, the present study fills the gap of limited studies addressing the issue of long-term orientation in the restaurant industry of Indonesia.